Design And Simulation Study Of Antenna For Wireless Body Area Network (Wban) - Mohamad Syahmi, Ismail (2022)
The rapid advancement of technology has led to an increase in the medical sector and the introduction of a new technology, namely the Wireless Body Network (WBAN). A wireless body network (WBAN) is a network of sensors installed on the human body. The term "WBAN" was introduced by Van Dam in 2001. For the design, a micro-band patch antenna is used because it is the best candidate for application to the body. This type of antenna has a radiation beam that is perpendicular to the ground plane (ground), making it able to protect body tissues from radiation [1]. This thesis describes antenna design and simulation for wireless body area networks (WBAN). This antenna is designed to operate at 2.45GHz (ISM band). The antenna performance will be tested in bending conditions, with a human body layer model to test the SAR value and a human body arm model to test the antenna performance when attached to the body. Design and analysis were done using CST Studio Suite 2019. All-important parameters for antenna design such as bandwidth, gain, VSWR, S-Parameter, return loss, and directivity can be shown in this project.